The Challenge of "Monomorphic" Mucoepidermoid Carcinoma-Report of a Rare Case with Pure Spindle-Clear Cell Morphology - Qu, Xinyi; Chew, Edwin Jun Chen; Selvarajan, Sathiyamoorthy; Wu, Bingcheng; Agaimy, Abbas; Petersson, Fredrik (Head and Neck Pathology, 2023)
BackgroundMucoepidermoid carcinoma is a malignant salivary gland tumor which, in most cases, is composed of variable proportions of mucous, epidermoid, and intermediate cells.MethodsWe report a case of parapharyngeal mucoepidermoid carcinoma with highly unusual ("monomorphic") light microscopic features as well as atypical immunohistochemical properties. Molecular analysis was performed using the TruSight RNA fusion panel.ResultsThe tumor featured heretofore undescribed histopathological features: sheets and nests composed of monomorphic neoplastic (plump spindle to epithelioid) cells with no mucous, intermediate, glandular/columnar, or any other cell type identified. The neoplastic cells displayed variable clear cell change and only expressed cytokeratin 7. Despite this non-classical morphology, the presence of the classical CRTC1::MAML2 fusion was demonstrated.ConclusionsMucoepidermoid carcinoma featuring a uniform ("monomorphic") population of neoplastic cells is a novel observation. A confident diagnosis of mucoepidermoid carcinoma can be made upon detection of the CRTC1/3::MAML2 fusion. Our case increases the spectrum of histopathological appearances that mucoepidermoid carcinoma may display.
CRIS-Team WoS Importer:2023-04-21